2013
DOI: 10.1183/09059180.00006613
|View full text |Cite
|
Sign up to set email alerts
|

New horizons in pulmonary arterial hypertension therapies

Abstract: Pulmonary arterial hypertension (PAH) is a fatal disease associated with vasoconstriction and vascular remodelling. There are three well-known pathways that contribute to the pathogenesis of PAH: endothelin, nitric oxide and prostacyclin. Treatments targeting these pathways are well established in clinical practice, such as endothelin receptor antagonists, phosphodiesterase type-5 inhibitors and epoprostenol. New treatments have been developed with the aim of improving efficacy and ease of administration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 92 publications
0
29
0
1
Order By: Relevance
“…It has a specific dynamic and can thus occur as acute dysfunction with prior normal functioning or be of a chronic, smouldering character, with tendency for occasional sudden aggravations. It is unquestionable that the generalised ED has a key role in the development of different cardiovascular diseases, being of significance in the occurrence and progression of arterial hypertension, atherosclerosis, coronary artery disease and heart failure [12,13]. In COPD, ED is linked with a more severe degree of disease, lower values of forced expiratory volume in 1 s (FEV1), and also with worse overall prognosis of pulmonary disease [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It has a specific dynamic and can thus occur as acute dysfunction with prior normal functioning or be of a chronic, smouldering character, with tendency for occasional sudden aggravations. It is unquestionable that the generalised ED has a key role in the development of different cardiovascular diseases, being of significance in the occurrence and progression of arterial hypertension, atherosclerosis, coronary artery disease and heart failure [12,13]. In COPD, ED is linked with a more severe degree of disease, lower values of forced expiratory volume in 1 s (FEV1), and also with worse overall prognosis of pulmonary disease [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These are the use of endothelin receptor antagonists and inhibitors of the enzyme 5-phosphodiesterase to boost the effect of endogenous NO on its receptor, the soluble guanylyl cyclase. These compounds, used alone or in different combinations and schedules, have revolutionized the treatment of this complex and fatal disease to the point that the long-term management with orally-active compounds is now being investigated and prostacyclin and nitric oxide receptor agonists are at present the subject of long-term clinical trials (76)(77)(78)(79)(80) . Furthermore, the proliferative nature of the disease, at least in part associated with the release of platelet-derived growth factor, has led to the development and use of different kinase inhibitors (79) .…”
Section: The Vascular Endotheliummentioning
confidence: 99%
“…The parameters mainly assessed were 6 min walking distance, PAP, pulmonary vascular resistance (PVR), cardiac index and a signifi cant improvement was observed in patients treated with riociguat. 8,20 A Phase IIb double blinded placebo controlled dose ranging study investigated the effi cacy of riociguat in patients with heart failure due to PH associated with left ventricular systolic dysfunction. The results of the study showed that there was no signifi cant improvement in the primary end point (6 min walking distance), but there were a signifi cant improvement in secondary end points.…”
Section: Clinical Trials Phase I Trialmentioning
confidence: 99%